ANALISIS KONSENTRASI TIMBAL PADA TANAMAN KUBIS (Brassica oleraceae L) DI KOTA TOMOHON - Sartika Fergina Rurut; D.M.F. Sumampow; Wiske Rotinsulu (Universitas Sam Ratulangi, 2019)
ABSTRACT This study aims to determine the concentration of lead in cabbge plants in Tomohon city. The results of this study are expected to provide information to the public about the amount of lead metal content in cabbage vegetables in Tomohon city. This research was conducted for 3 (three) months, from June to September 2018, the location of sampling in Tomohon City and then analyzed at the Baristand Laboratory. This research was conducted in a survey using a purporsive sampling method by examining samples of cabbage plants that are off the highway and cabbage that are cultivated far from the highway. Each location was taken as many as 5 plants. Pb samples were tested for comparison, wich were analyzed using the Atomic Absorpation Spectrophotometer. The results of this study indicate that lead concentrations (Pb) in cabbage plantations in Tomohon are detected with concentration values that are still below the standard for heavy metal contamination or are still below the maximum limit. Keywords: Lead, Cabbage